Filtration Analysis of Microparticles Using Paper‑Based Microfluidics - Bhuvaneshwari, K. S.; Jeroish, Zachariah Ezhilnavaroji; Futane, Abhishek; Fahmi, Samsuri; Narayanamurthy, Vigneswaran (Springer, 2024)
A virus is a sub-microscopic infectious organism that causes diseases in humans, animals, and plants resulting in morbidity and may cause mortality. Proper diagnosis is necessary to initiate the treatment and pave the way to eradicate the viral infection. The current diagnostic kits for nucleic acid amplification assay, blood filtration, single-cell analysis are highly accurate, even though the procedure necessitates large sample volumes, complicated fabrication steps, time-consuming processes, and high costs. The filtration of viral samples from the blood is a tedious process. In this research, we have presented a home-based fabricated paper microfluidic chip to effectively filtrate viral particles from the sample to facilitate the nucleic acid amplification assay. The filtration analysis was exhibited for lateral and vertical flow paper chips fabricated via laser printing and polyethylene terephthalate (PET) encapsulation that circumvents the necessity of a traditional wax printer and hot plate. The results convey that the vertical flow paper chip with grade 4 inlet and outlet filters 98.57% of unnecessary particles from the sample. The paper-based microfluidic chip developed in this research is simple, easy to fabricate, and inexpensive to access in underdeveloped countries. The paper chip can pave the way for applications like lab-on-chip devices, POC assays, rapid nucleic acid amplification tests, cell cultures, and biomolecular research.